Review Study about Portable and Wearable Artificial Kidney Systems - Aljanabi, Fanar; Lafta, Hassanain Ali Hussein (Al-Nahrain Journal for Engineering Sciences, 2024)
Kidney renal failure is a life-threatening disease in which one or both kidneys are not functioning normally. The only available treatment other than a kidney transplant is to start on dialysis sessions, whether it is peritoneal or Hemo-dialysis[1].For some patients, the dialysis procedure is an exhausting and sometimes expensive trip to the specialized dialysis centers since it must be done about three times a week, depending on the physician’s decision depending on the glomerular filtration rate of the kidneys[2-4].Different researchers have made many attempts over the years to replace conventional dialysis machines with more accessible at-home dialysis systems to provide patients with comfortable treatment sessions at the time they want without the need to change their lifestyle to fit the dialysis center’s schedule.A review of the critical methods utilized in the creation and application of a portable dialysis machine that resembles the traditional dialysis center devices was conducted using a number of prior studies (research conducted between 2009 and 2024); the goal of all studies was to create a device that consists of filtering system, detection system to ensure there is no blood leakage and all parameters are within the acceptable limits, alarm system, and dialysate regeneration system, and each method will be described precisely in this review.As a result, the discussed studies found that using peristaltic pump pumps with a phase difference by half cycle between blood and dialysate will cause a higher urea clearance rate; multiple studies focused on the modification of the dialyzing filter to find that using Polyethene glycol surface-modified silicon nanopore membranes, dual-layer hollow fiber membranes, the use of BRECS cell therapy, carbon activated blocks, all contributed highly in enhancing the dialyzing process providing the patients with highly efficient blood purification session.